Perancangan User Interface Dan User Experience Aplikasi Kacamata Menggunakan Metode Human Centered Design - Alfian, Rian; Maruf Nugroho, Imam; Raymond Ramadhan, Yudhi (UNIKA Santo Thomas, 2023)
Optik Halim Purwakarta is a company engaged in optical sales, providing various kinds of glasses, frames, contact lenses, lens cleaning fluids and other optical accessories. Currently Optik Halim Purwakarta has difficulty receiving orders from outside the region. That's why Optik Halim Purwakarta plans to develop customer applications in the future. The purpose of this research is to design the user interface and user experience for the optical glass application. Human Centered Design (HCD) is a system design and development approach that aims to make systems more usable through the application of human or ergonomic knowledge and factors. The Human Centered Design (HCD) method consists of five steps: understanding and determining the context of use, determining user needs, generating design solutions, and evaluating design solutions. Based on the design and testing methods used by researchers to conduct this research. From the results of this study, the Halim Optik Purwakarta application was developed with an average System Usability Scale (SUS) score of 82.5, where the score is included in category B and can be accepted by users.